THE EFFECT OF REGIONAL ORIGINAL INCOME AND CONSIDERATION FUNDS ON THE ALLOCATION OF THE CAPITAL SHOPPING BUDGET IN THE GOVERNMENT OF THE DISTRICT / CITY IN NORTH SUMATERA AND EAST JAVA WITH ECONOMIC GROWTH AS A MODERATING VARIABLE - Afnisah, Anggi (International Journal of Public Budgeting, Accounting and Finance, 2020)
This study aims to determine the effect of Local Own-source Revenue and Fiscal Balancing Funds (general allocation fund, special allocation fund, revenue sharing fund) on the allocation of capital expenditure budgets in District / City Governments in North Sumatra and East Java. In addition, this study will also examine economic growth variables which are used as moderating variables. This type of research is carried out based on associative research. This research was conducted in Regency / City Government in North Sumatra and East Java Provinces. By using purposive sampling technique, the number of research samples known is 34 districts / cities. This research was conducted for the period 2010-2018. The type of data used is secondary data and data analysis techniques used in this study are Panel Data Regression Analysis and Interaction Test. The results obtained in this study indicate that the Local Own-source Revenue (LOR), General Allocation Fund (GAF) and Revenue Sharing Fund (RSF) have a positive and significant effect on the allocation of capital expenditure budget. In addition, the moderating variable used in this study is that economic growth can be proven to be a moderating variable in the effect of Local Own-source Revenue and Special Allocation Fund. While the General Allocation Fund and Revenue Sharing Fund are not